Investigating the Karakoram Anomaly and Its Impacts on Water Supply in Pakistan - Shahid Ali; Muhammad Hasnain (`, 2025)
The Karakoram Anomaly is that many glaciers in Pakistan’s Karakoram Range have either remained stable or even advanced over the last few decades. This is in contrast to the rest of the world’s glaciers which, under the influence of global warming, are retreating. This research focuses on the unbalancing climatic, topographic, and glaciological factors of Pakistan’s water resources. It is based on a qualitative, integrative approach combining literature review, climate and hydrological data analysis, remote sensing imagery, and field observations conducted in Gilgit-Baltistan during 2022 and 2023. The results suggest that advanced winter precipitation from westerly disturbances, stable to cooler summer temperatures, and extensive debris cover, alongside high-altitude microclimatic shielding, glaciological factors have a positive impact on mass balance. Through examining river discharge records and while interviewing some stakeholders, the research shows that the glacier anomaly is the main reason why there are constant flows of water into the Indus Basin. This in turn sustains irrigation, hydropower, and domestic water supply. This stability, however, is fragile: any minor increase in temperature or precipitation could increase melt, change river systems, and increase the chances of floods or shortages during the dry season. The research focuses on the Karakoram Anomaly, describing the region’s climate-buffering capabilities and climate-change-induced threats while calling for higher inertia in the region’s water management policies. It highlights the need for Pakistan’s glacier advance monitoring, adaptive water management, and integrated resilience planning. Keywords: Karakoram Anomaly, Deltas, climatic change, semi-arid regions, Hindukush-Karakoram-Himalaya (HKH), water-supply